2017
DOI: 10.1371/journal.pone.0183313
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive intraoperative fluid optimisation algorithm improves outcomes in patients undergoing pancreaticoduodenectomy: A prospective multicentre randomized controlled trial

Abstract: We aimed to evaluate perioperative outcomes in patients undergoing pancreaticoduodenectomy with or without a cardiac output goal directed therapy (GDT) algorithm. We conducted a multicentre randomised controlled trial in four high volume hepatobiliary-pancreatic surgery centres. We evaluated whether the additional impact of a intraoperative fluid optimisation algorithm would influence the amount of fluid delivered, reduce fluid related complications, and improve length of hospital stay. Fifty-two consecutive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
3
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 53 publications
1
62
3
2
Order By: Relevance
“…Several studies have reported how to administer fluid in patients undergoing major abdominal surgeries, including open gastrectomy. Small trials have shown that a restrictive fluid regimen reduced the complication rate compared with a liberal fluid management regimen during elective surgery [3,4]. The restriction of fluid to achieve a zero balance is also an important element of the enhanced recovery after surgery (ERAS) protocol [19]; however, a recent study that compared liberal fluid therapy with restrictive fluid therapy in approximately 3000 patients undergoing abdominal surgery reported that restrictive therapy was not superior to liberal therapy, and it also increased the incidence of AKI [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported how to administer fluid in patients undergoing major abdominal surgeries, including open gastrectomy. Small trials have shown that a restrictive fluid regimen reduced the complication rate compared with a liberal fluid management regimen during elective surgery [3,4]. The restriction of fluid to achieve a zero balance is also an important element of the enhanced recovery after surgery (ERAS) protocol [19]; however, a recent study that compared liberal fluid therapy with restrictive fluid therapy in approximately 3000 patients undergoing abdominal surgery reported that restrictive therapy was not superior to liberal therapy, and it also increased the incidence of AKI [20].…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesiologists select the appropriate fluid type for the patient and administer the appropriate amount of fluid. Previous studies have shown that the type of fluid therapy is associated with postoperative recovery and prognosis [1][2][3][4]. For successful fluid therapy, it is helpful to quantify how the administered fluid is distributed and eliminated from the body.…”
Section: Introductionmentioning
confidence: 99%
“…Prevailing evidence from our research group and others, has led to the notion of the "protocolised" perioperative "fluid-restrictive" approach [28][29][30] in order to reduce postoperative morbidity, including AKI. In this regard, our findings are consistent with the existing evidence reinforcing a strong association between fluid volume [31][32][33][34][35][36][37] and chloriderich fluid type [38][39][40][41] , and risk of AKI.…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…GDFT involves titrating small boluses of intravenous fluid (250 mL) against stroke volume measured on a cardiac output monitor in order to optimise intravascular haemodynamics on an individual basis. Adopting this approach to fluid prescription post-HPB surgery could lead to a reduction in overall intravenous fluid administered and consequent improvement in outcomes [31]. It should be noted though, that when using GDFT there is a risk of harm in some patient subgroups if the overall intravenous fluid input remains high [32].…”
Section: Discussionmentioning
confidence: 99%